The other side of the coin: A case study on the impact of financial autonomy on irrigation management performance in the Philippines - Oorthuizen, J.; Kloezen, W.H. (1995)
The paper assesses the impact of the removal of operating subsidies to the Philippine National Irrigation Administration on the management performance of a small canal irrigation system in Southern Luzon. It shows that in this case the creation of financial autonomy of the agency did not fully engender the often assumed positive effects regarding both accountability relationships and irrigation management performance. The conclusions specify a number of issues related to the theory of financial autonomy which require further study.